DEMOGRAPHY AND RISK FACTORS IN PATIENTS WITH ACUTEST ELEVATION MYOCARDIAL INFARCTION UNDERGOING PRIMARY PERCUTANEOUS INTERVENTION IN A TERTIARY CARE CENTER OF PAKISTA - Saif, Mohsin; Khan, Hamid Sharif; Javed, Asim; Khan, Kumail Abbas; Khalid, Waqas; Javaid, Syed Yasser (Pakistan Armed Forces Medical Journal, 2019)
Objective: To study the demography and risk factors in patients with acute ST elevation myocardial infarction undergoing primary PCI in a tertiary care center of Pakistan. Study Design: Retrospective cross-sectional study. Place and Duration of Study: Rawalpindi Institute of Cardiology from Jan 2017 to Dec 2017. Methodology: All patients diagnosed with acute ST elevation myocardial infarction (STEMI) and selected for primary PCI between Jan 2017 to Dec 2017 were included in the study. The Statistical package for social science SPSS version 11 was used for data analysis. Continuous variables are expressed as mean ± SD. The traditional cardiovascular risk factors (smoking, hypertension, and diabetes mellitus) were noted as percent. The regions of infarction (anterior, inferior and combination) and the left ventricular ejection fraction in percentage were also documented. Descriptive analysis was mainly used. Results: Total of 818 patients diagnosed with acute ST elevation myocardial infarction (STEMI) and selected for primary PCI between. The mean age was 51.1 ± 11.4 years (range 23-91 years) with staggering 699 (85.5%) patients being male. Majority (31%) of the patients (n=341) were hypertensives and an almost equal percentage 30% (n=331) were chronic smokers. 15% of the patients (n=166) were diabetic and 9% of the patients (n=95) had a strong family history of ischemic heart disease. 7% of the patients (n=77) had dyslipidemia and interestingly 8% of the patients (n=85) were both hypertensives and diabetics. Conclusion: The potentially modifiable risk factors, especially smoking, had high prevalence in patients with STEMI living in around Rawalpindi district. Similarly uncontrolled hypertension also contributed to acute STEMI in about one third of the patients.